Phenol removal capacity of RO with and without pre-treatment - Ipek, U (Elsevier Advanced Technology, 2004)
The effect of traditional pre-treatment methods, such as depth filtration and granular activated carbon (GAC), on the phenol removal capacity of reverse osmosis (RO) was investigated. Two experimental series were performed in the pH range of 4-9. Firstly, a phenol- containing water sample was passed through a RO membrane alone. A sample was then passed through a depth filter and a GAC unit prior to it being passed through the RO membrane. The results indicate that the best RO phenol removal efficiency occurs with GAC pre-treatment. The phenol concentration in the RO effluent was reduced to less than 0.25 mg/l.
Keywords: Reverse-Osmosis